2000
DOI: 10.1055/s-0038-1634249
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Specificity and Stability of Human EEG: Comparing a Linear vs a Nonlinear Approach

Abstract: Abstract:We have applied the so-called “unfolding dimension approach’’ to reanalyze an earlier longitudinal EEG study. Both linear and nonlinear approaches show that the EEG comprises a static, person-specific part upon which nonstatic and state-specific parts are superimposed. The intraindivi-dual specificity and stability of the genetic part are similar between methods. This is assessed by comparing the outcome of a person to his own outcomes at later times (14 days and 5 years later). The nonlinear method r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Specifically, we recorded task-independent resting electroencephalography (EEG) of 87 participants before measuring their everyday pro-environmental behaviour over the course of five days. Measuring an individual’s baseline cortical activation with EEG is an ideal neural trait measure because it is unique to an individual (recognising a person based on their pattern of brain electrical activity at rest is possible in up to 99% of cases) and relatively stable over time, with a retest-reliability of up to 0.80 after 5 years 2628 . Prior studies could show that this measure of neural traits helps to explain variance in expertise (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we recorded task-independent resting electroencephalography (EEG) of 87 participants before measuring their everyday pro-environmental behaviour over the course of five days. Measuring an individual’s baseline cortical activation with EEG is an ideal neural trait measure because it is unique to an individual (recognising a person based on their pattern of brain electrical activity at rest is possible in up to 99% of cases) and relatively stable over time, with a retest-reliability of up to 0.80 after 5 years 2628 . Prior studies could show that this measure of neural traits helps to explain variance in expertise (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Task-independent EEG at rest constitutes an ideal neural trait measure due to its high specificity (i.e., the extent to which an EEG pattern is uniquely associated with a given person; Dünki et al 2000; Näpflin et al 2007) and high stability over time (e.g., Dünki et al 2000; Näpflin et al 2007; Cannon et al 2012). In addition, it has been used to reveal sources of individual differences in time preferences (Gianotti et al 2012), risk preferences (Gianotti et al 2009; Studer et al 2013), and social preferences (Knoch et al 2010; Baumgartner et al 2013; for a review, see; Nash et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One such ideal trait measure is the task-independent neural baseline activation measured by resting electroencephalography (EEG). Resting EEG can be measured objectively and demonstrates both high temporal stability (Cannon et al, 2012;Dünki, Schmid, & Stassen, 2000;Williams et al, 2005) and high specificity (i.e., the extent to which a given EEG pattern uniquely belongs to a given person; Näpflin, Wildi, & Sarnthein, 2007). Studies investigating its temporal stability revealed test-retest reliabilities of up to 0.8 over a period of 5 years, while those exploring its specificity revealed recognition rates of up to 99%.…”
mentioning
confidence: 99%